Developing Material for Teaching Paragraph Writing Using Technological Pedagogical and Content Knowledge (TPACK) - Farikah Farikah (Institut Agama Islam Negeri Palopo, 2021)
This design based research was aimed to to develop materials for teaching paragraph writing using TPACK approach. The students of English Department of Tidar University (Untidar) were involved as the subject of the reserach. This research was conducted in four phases. They were analysis of practical problems, development of solutions, iterative cycles of testing and refinement of solution, and reflection to produce design and principles. The results of the research indicated that technological pedagogical and content knowledge approach material was needed for teaching paragraph writing. These findings recommended this TPACK approach-based material could be adopted as materials for teaching paragraph writing.